Pemanfaatan Media Audio Visual pada Kegiatan Bercerita dalam Meningkatkan Perkembangan Bahasa Anak di TK Khalifah 23 Palembang - Mareta, Edlien; Andika, Windi Dwi; Munnafiah, Nida’ul (Sahabat Akademia Group, 2024)
Language is an important component in early childhood development. Thus, a stimulus is needed to increase this development with various activities, namely storytelling activities using audio-visual media. This research aims to be one way to improve children's abilities in language development through storytelling activities through audio-visual media. This research will be carried out in 2 cycles, using classroom action research methods, improvement plans, objects, and reflection. The place where this research was carried out was TK Khalifah 23 Palembang. Based on the results of research activities that have been carried out, the results obtained are cycle I children's language abilities from a total of 15 children, 8 children (53%) have developed very well, 4 children (27%) have developed as expected. 3 children (20%) have started to develop. In the improvement cycle II, the results obtained were that 13 children (87%) had received very good grades, 2 children (13%) had obtained good grades and were developing according to expectations. So we can conclude that storytelling activities using audio-visual media carried out at TK Khalifah 23 Palembang have been able to improve children's language skills. What can be seen from each cycle is that there is a very significant increase.